Acción de la tetraciclina sobre la elefantitis en Venezolana experimental - comunicación preliminar - Negrette, Américo; Soto, Armando; Ryder, Slavia (Investigación Clínica, 2013)
Mice were inoculated wit 10 LDso of venezuelan equine encephalitis virus and 1.5 mgs. Daily of tetracycline. At the end of the experiment almost half of the group which had received virus and antibiotic were alive while those with virus only had all died.